Residuum oralności a wizja świata w romansie staropolskim - casus Fortunata - Bobrowska, Aleksandra (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2015)
The article discusses the issue of the co-existence and correlation of different traditions – orality and literacy – in the 16th century old-Polish romance. The deliberations are based on the case study of Fortunat, which is a translation of a popular German novel. One of the key assumptions made in the article is the fairy-tale character of Fortunat, indicating this work’s connections with primarily oral forms of narration. The study of romance, including among others the analysis of composition, narration and characterization, shows that at the beginning of print culture the marks of oral poetics are interwoven with features of literacy. The ultimate question raised by the article is, however, what are the consequences of shifting from orality to literacy to the vision of the world as depicted in the romance.
Keywords: oralność; romans staropolski; opowieść